Struktura zastopanosti matematičnih dejavnosti v slovenskih vrtcih - Nudl, Andreja (Matematika v šoli, 2012)
Preschool mathematics can be divided into three different content areas: arithmetic and algebra, geometry and measurement, and other contents. We were interested in the quantity of mathematical activities in which children are engaged in Slovenian kindergartens. We have also described the ratio in which specific contents were observed. We analysed 130 portfolios of future preschool teachers and discovered 800 different types of activities. In the paper we analysed the distribution of different content areas and offered some suggestions for improvement of practice in preschool institutions.
Keywords: matematika; predšolska vzgoja; vsebina vzgoje in izobraževanja